cho (a+b+c)^2=a^2+b^2+c^2 chứng minh rằng 1/a^3+1/b^3+1/c^3=3/abc

cho (a+b+c)^2=a^2+b^2+c^2
chứng minh rằng
1/a^3+1/b^3+1/c^3=3/abc

2 bình luận về “cho (a+b+c)^2=a^2+b^2+c^2 chứng minh rằng 1/a^3+1/b^3+1/c^3=3/abc”

  1. Giải đáp+Lời giải và giải thích chi tiết:
    (a+b+c)^2 =a^2 +b^2 +c^2
    <=>a^2 +b^2 +c^2 +2ab+2bc+2ca=a^2 +b^2 +c^2
    <=>2ab+2bc+2ca=a^2 +b^2 +c^2 -a^2 -b^2 -c^2
    <=>2(ab+bc+ca)=0
    <=>ab+bc+ca=0
    <=>(ab)/(abc)+(bc)/(abc)+(ca)/(abc)=0/(abc)
    <=>1/c+1/a+1/b=0
    <=>1/a=-(1/b+1/c)
    Ta có : 1/(a^3)+1/(b^3)+1/(c^3)
    = -(1/b+1/c)^3 +1/(b^3 )+1/(c^3)
    = -(1/b+1/c)(1/(b^2)+1/(c^2)+2/(bc))+(1/b+1/c)(1/(b^2)-1/(bc)+1/(c^2))
    =(1/b+1/c)[-(1/(b^2)+1/(c^2)+2/(bc))+1/(b^2)-1/(bc)+1/(c^2)]
    =(1/b+1/c)(-1/(b^2)-1/(c^2)-2/(bc)+1/(b^2 )-1/(bc)+1/(c^2))
    =(1/b+1/c) . (-3/(bc))
    =-(1/b+1/c) . 3/(bc)
    =1/a . 3/(bc)=3/(abc)(đpcm)

    Trả lời

Viết một bình luận

Câu hỏi mới